Properties of Electrolytic Sterilization System of CNT Composit Cathode - Hee Han, Doo; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: Hydrogen, which can be produced in abundant water, is attracting attention as a new energy source. This paper describes the application of electrolyzed hydrogen water as disinfected water and suggests application fields.Methods/Statistical analysis: CNT based composites were used instead of expensive platinum or iridium alloys to develop the cathodes of electrolysis devices. The anode was made of a Ti-Ru alloy having excellent durability and conductivity.Findings: Electrolysis device was constructed and tap water electrolysis was performed, and it was fit to drinking water standard. In addition, harmful substances and bacteria were completely removed. As a result of applying it to the economic boats of ginseng, the growth rate was three times higher than that of soil cultivation and prevented root rot. It also showed excellent sterilization and cleaning ability when used for slaughtered pork.Improvements/Applications: This device is excellent in disinfection and decomposition ability and is considered to be suitable for wastewater treatment that occurs in fruit washing and Haitai processing.Â